STRATEGI INOVATIF MELALUI VIDEO ANIMASI CANVA: MENINGKATKAN PEMAHAMAN BAHASA INGGRIS ANAK TERHADAP MATERI ANIMALS DI KELAS V SDN 101766 BANDAR SETIA - Melisa Dita Aqila; Erika Elisabet Siagian; Zikra Anastasya Azzahra; Nella Trisnauli Hutagalung; Deyrizky Parinduri; Nanda Ramadani (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
The purpose of this study is evaluates the effectiveness of Canva-based animated videos in enhancing the English vocabulary comprehension of 5th-grade students at SDN 101766 Bandar Setia on the Animals topic. Using a qualitative approach with an exploratory method, data were collected through observation and interviews. The results indicate that this media significantly improves student comprehension, as evidenced by their ability to name, understand, and read vocabulary more fluently. Additionally, students demonstrated higher learning motivation. These findings support the Dual Coding Theory (Paivio, 1986) and Constructivism Theory (Vygotsky, 1978), which emphasize the importance of visual-verbal integration and active student engagement in learning.